The contribution of academic research to innovation and growth - Reinhilde Veugelers (WWWforEurope, 2014)
To better understand how academic research can contribute to innovative growth and to assess how Europe is and could be doing in this respect, we review the analysis and evidence of business science links and Europe's record on this. The evidence and analysis shows that the link between science and industry is neither direct nor obvious. When looking at the evidence for Europe, there is a general lagging behind relative to the US, particularly on academic patenting and university spin-offs. Patenting and licensing is only two of a number of pathways for the transfer of knowledge from universities to industry, and perhaps not even the best forms. Student & researchers' mobility from academe to industry is a critical mechanism to transfer knowledge from the university to industry, particularly when the knowledge to be transferred is hard to codify and is embodied in human capital as is the case for science-based knowledge. Although this is an area of great importance to the study of the innovation process, only recently research has started to attempt to trace researchers' intersectoral mobility When looking for ways to improve the transfers from science to innovation, most of the attention in the academic literature and policy is on finding the critical success factors on the science side. Most of this analysis looks at academic patenting and faculty spin-offs and comes from best US practices. These include proper intellectual property right regimes, where Bayh-Dole type of reforms which allocate property rights to the university, are considered to have cleared the path towards tech transfer in the US. Other best practices include having in place incentive schemes for tech transfers, with a fair share for researchers in royaltees and spin-offs and having in place a dedicated technology transfer office, which critical scale, expertise and experience in mediating technology transfer. But perhaps the most important success factor for tech transfer identified is the quality of the research faculty and their created ideas. Overall, the most salient policy recommendations that stems from the analysis is that policy makers looking for ways to improve the contribution of universities to innovation based growth, should take a long-term perspective for developing an industry-science eco-system, avoiding the temptation of quick “success stories”. A particular dangerous policy practice is a target focusing only on the commercialization of university technologies through academic patenting and spin-offs, ignoring the broader contribution to economic development with other pathways, most notably the research based training and mobility of human capital from universities. Policy makers should be more “innovative” in their search for effective policy interventions, venturing beyond the classic spin-off and incubator programs. At the same time, they should be more serious about evaluating their new and existing instruments. To progress, policy makers should support more systematic data collection and analysis on the various pathways for universities' contribution to economic prosperity.
Keywords: O31; O38; 330; Academic research; Clusters; Innovation; Innovation policy; New technologies; Patents; Research